Peritoneal Keratin Granulomatosis Associated with Endometrioid Adenocarcinoma of the Uterine Corpus in a Woman with Polycystic Ovaries: A Potential Pitfall-A Case Report and Review of the Literature - Helen J. Trihia; Maria Papazian; Natasa Novkovic; John Provatas; Sotiria Tsangouri; Dimitrios C. Papatheodorou (Hindawi Limited, 2017)
Peritoneal keratin granulomatosis is a rare condition included under granulomatous lesions of the peritoneum. It can be secondary to neoplasms of the female genital tract and can mimic carcinomatosis intraoperatively. A case of a 40-year-old woman with a history of polycystic ovaries and a chief complaint of vaginal bleeding is presented. She was diagnosed with endometrioid adenocarcinoma with squamous differentiation in endometrial curettings. Intraoperatively, many peritoneal nodules were found, interpreted as peritoneal carcinomatosis. The woman underwent a total abdominal hysterectomy with bilateral salpingo-oophorectomy, omentectomy, bilateral pelvic lymphadenectomy, and appendicectomy. Multiple biopsies were taken, as well as peritoneal washings. Microscopic examination revealed multiple keratin granulomas on the serosal surface of the ovaries, fallopian tubes, appendix, and omentum. Lymph node metastasis was not found. Peritoneal keratin granulomas (PKGs) have been reported in cases of endometrioid adenocarcinoma with squamous differentiation of the uterine corpus, ovary, and atypical adenomyoma. It should be noted that the prognosis of cases of peritoneal keratin granulomas without viable tumor cells is favourable and that the histologic examination is essential for its diagnosis. We report a case of PKG in a patient with endometrial carcinoma with squamous differentiation, being the first in a woman with polycystic ovaries.